Defense Automated Neurobehavioral Assessment Accurately Measures Cognition in Patients Undergoing Electroconvulsive Therapy for Major Depressive Disorder. Issue 1 (March 2018) - Hollinger, Kristen R.; Woods, Steven R.; Adams-Clark, Alexis; Choi, So Yung; Franke, Caroline L.; Susukida, Ryoko; Thompson, Carol; Reti, Irving M.; Kaplin, Adam I.
Abstract : Objectives: The Defense Automated Neurobehavioral Assessment (DANA) is an electronic cognitive test battery. The present study compares DANA to the standard Mini-Mental State Examination (MMSE) in subjects undergoing electroconvulsive therapy for the treatment of major depressive disorder. Methods: Seventeen inpatient subjects in the Johns Hopkins Hospital Department of Psychiatry were administered longitudinal paired DANA and MMSE tests (7.6 ± 4.1 per patient) from January 10, 2014 to September 26, 2014. Regression analyses were conducted (with or without MMSE scores of 30) to study the impact of the MMSE upper limit, and within-subject regression analyses were conducted to compare MMSE and DANA scores over time. Results: Statistically significant relationships were measured between DANA and MMSE scores. Relationships strengthened when MMSE scores of 30 were omitted from analyses, demonstrating a ceiling effect of the MMSE. Within-subject analyses revealed relationships between MMSE and DANA scores over the duration of the inpatient stay. Conclusions: Defense Automated Neurobehavioral Assessment is an electronic, mobile, repeatable, sensitive, and valid method of measuring cognition over time in depressed patients undergoing electroconvulsive therapy treatment. Automation of the DANA allows for more frequent cognitive testing in a busy clinical setting and enhances cognitive assessment sensitivity with a timed component to each test.